3-(3-Chloro-2-hydroxyphenyl)-1-phenyl-1H-pyrazole-4-carbaldehyde - Lokhande, P.; Ali, Hapipah Mohd; Khaledi, H.; Hasanzadeh, K. (International Union of Crystallography, 2011)
In the title compound, C16H11ClN2O2, the pyrazole ring makes dihedral angles of 11.88 (13) and 22.33 (13)degrees with the 3-chloro-2-hydroxybenzene group and phenyl rings, respectively. The phenolic hydroxy group forms an intramolecular O-H center dot center dot center dot N hydrogen bond with the imine N atom of the pyrazole unit. The formyl group is virtually coplanar with the pyrazole ring [dihedral angle = 4.5 (19)degrees] and acts as an acceptor in an intramolecular C-H center dot center dot center dot O hydrogen bond closing seven-membered ring. In the crystal, adjacent molecules are linked through C-H center dot center dot center dot O hydrogen bonds into infinite chains along the b axis.